MAIN PROBLEMS IN THE DEVELOPMENT OF SMALL AND MEDIUM BUSINESSES IN UZBEKISTAN AND THEIR SOLUTIONS - Toir Xolmirzayev; Nozima Meyliyeva (Web of Journals Publishing, 2025)
The article notes that small and medium businesses as an important sector of the economy of Uzbekistan play an important role in providing employment, developing local production and increasing export potential.
Keywords: Small and medium businesses, business problems, financial support, tax incentives, innovative development, market infrastructure, technology implementation, legislative reforms.